Functional brain imaging using near-infrared spectroscopy - Ananth Sandhya (2013)
The human prefrontal cortex (PFC) plays an important role in selecting thoughts and actions according to internal goals. This function of the PFC is known as cognitive control. The signals from the PFC guide the flow of activity through the neural pathways that bring about correspondence between inputs, internal goals and response required to perform the task. Brain activity is associated with a series of physiological processes. Parameters such as decrease in deoxyhemoglobin, increase in oxyhemoglobin and cerebral blood volume (CBV) indicates increase in neural activity. These physiological changes can be captured using Near-infrared Spectroscopy (NIRS). In recent years it has been extensively used to study the functional aspects of human brain due to its non-invasive nature.